SISTEM INFORMASI GEOGRAFIS WARISAN BUDAYA NON FISIK DI JAWA TENGAH DENGAN MEMANFAATKAN GOOGLE MAPS API (Information Technology and Telematics, 2012)
Abstract - Culture heritage is a product or culture result the physical culture from traditions different and spiritual achievements has values ​​in the past it is be principal element in the identity of a group or nation (Davidson 1991:2). Culture heritage is divided into two physical (tangible) and non-physical (intangible). The physical culture heritage including sites, historical places, and landscape, water landscapes, ancient or historic of buildings, statues of heroes, while for non-physical cultural heritage includes tradition, arts, folklore, native language, oral history. Talk about the culture heritage of Central Java having many cultural heritages, especially cultural heritage non-physical art. Therefore it is necessary documentation in order to not be disappearing. A form of documentation is do mapping using Geographic Information System. Geographic Information Systems (GIS) is information systems used to input, store, retrieve, process, analyze and produce data geographically referenced or geospatial, to support decision making in the planning. By using a Geographic Information System (GIS) it will be easier for decision makers to analyze the data. Along with the development of digital media and forms of communication, GIS applications also develop with more accessible and facilitate the spread of information. It is characterized by emergence variety of online maps, one of which Google Maps. The use of Google Maps that can be customized by providing an API that can be utilized to form a SIG website. In this thesis will discuss about the necessary steps in creating a web-based GIS applications using the Google Maps API. Keywords : Cultural Heritage, Central Java, GIS, Google Maps API, web